ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LITERASI KEUANGAN: Studi Pada Mahasiswa Institut Ilmu Sosial dan Manajemen STIAMI - Mohammad Sofyan; Iin Andrayanti (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2023)
This study aims to determine the factors that affect the financial literacy of STIAMI Institute of Social Sciences and Management students with a sample of 179 students based on snowball sampling techniques. Data analysis technique using second order confirmatory factor analysis with Smart-PLS application version 3.29. The results showed that the dominant factors influencing financial literacy were: (1) Money and Transactions; and (2) Financial Planning and Management. Meanwhile, factors that need to be improved related to financial literacy are: (1) Financial Landscape; and (2) Risks and Profits. Things that need to be improved so that student literacy increases are (1) knowledge of monitoring income and costs in meeting their needs; (2) understanding taxation; and (3) understanding interest rates